Key Practices for Incorporating Sustainability in Project Management from the Perspective of Brazilian Professionals - Vasco-Calle, D (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Project management has incorporated sustainability concepts, but their relationship is still widely discussed. In this article, we research key practices for incorporating sustainability in project management from the perspective of 919 Brazilian professionals with experience in the field. We used factor analysis to explore the relationship between 37 sustainability practices. The results showed that these sustainability practices can be grouped into five key practices: environmental efficiency, compliance, social responsibility, continuous improvement and lessons learned, and project success. We also used word clouds to highlight the main themes in the practices encompassed by each key practice. The results contribute to project leaders and other project management professionals directing their efforts toward improving sustainability actions related to these practices in project management processes. © 2023 by the authors.